The possibility of the sublime : aesthetic exchanges - Aagaard-Mogensen, Lars, 1944- (Cambridge Scholars Publishing, 2017)
The notion of the sublime, used to describe a particular kind of overwhelming or exhilarating aesthetic experience, has garnered a great deal of attention by philosophers, critical theorists and literary scholars. In the midst of this growing body of literature, Professor Jane Forsey published an article asking whether an aesthetic theory of the sublime is even possible, and argued provocatively in the negative. Claiming that efforts to explain the sublime inevitably result in theories that are either contradictory or incoherent, Forsey posed a challenge to anyone who takes the sublime serious.